The Influence of Reciprocal Teaching Learning Model on the Critical Thinking Abilities of Fourth-Grade Students in Science Subjects at SDN 32 Cakranegara - Putri Yunita; Husniati Husniati; Mohammad Liwa Ilhamdi (Syntax Idea)
The purpose of this study was to determine the effect of the reciprocal teaching learning model on the critical thinking ability of students in class iv science content of Elementary School 32 Cakranegara. This research design is an experimental design used is Quasi Experimental Design with Nonequivalent Control Group Design pattern. This study uses 4 stages of Reciprocal Teaching research, namely, summarizing, questioning, predicting, and clarifying. The research was conducted at Elementary School 32 Cakranegara, Sandubaya District, Cakranegara. Data collection tools use observation and tests. The results showed that the Reciprocal Teaching Method had a significant effect on students' critical thinking skills. Based on the calculation of the hypothesis test using the independent samples t-test formula assisted by the statistical application SPSS 16.0 for windows obtained data that tcount (6.496) > t-table (1.998). That is, Ho is rejected Ha accepted, namely the Reciprocal Teaching method affects students' critical thinking skills in science lesson content.